Marriage Aqd Validity Through Electronic Media Based on Positive Law and Islamic Law - muslimah, muslimah; Septyanun, Nurjannah; Erwin, Yulias (Universitas Muhammadiyah Bima, 2023)
Telecommunications technology currently has a major effect on changes in human interaction throughout their lives, including electronic media. This rapid presence of telecommunications facilities clearly affects marriage implementation in Indonesia, namely with a long-distance marriage contract (aqd) through electronic media. Thus, this raises the pros and cons about its validity in the community. This phenomenon raises issues about its validity in positive law and Islamic fiqh. The objective of this research was to contribute conducive thoughts regarding aqad nikah via electronic media and its validity in positive law and Islamic fiqh. Due to the impact of this matter, the position of marriage aqd through electronic media has not been known about its validity. Using normative legal research with conceptual, statutory and case approaches. The results of this study showed that long-distance marriage with a marriage aqd by electronic media was still valid because it clearly fulfilled an implementation's terms and conditions, both according to Islamic Fiqh Law and according to Law Number 16 of 2019 on the amendment of Law Number 1 of 1974 concerning Marriage was legal and also looked at Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Electronic Information and Transactions.